Samoocena i wartościowanie kompetencji nauczycieli-terapeutów w przestrzeni edukacyjnej uczniów ze specjalnymi potrzebami edukacyjnymi – doniesienie z badań - Olechowska, Agnieszka (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The educational therapist is a person who in a public educational system is responsible for conducting research and diagnostic activities of students with developmental disorders and deviations or specific learning difficulties, conducting remedial and other therapeutic classes, to take preventive actions as well as supporting teachers, educators, educational groups and other professionals in providing psychological and pedagogical assistance. Because of this tasks teacher-specialist in educational therapy should present a broad professional competence. The article presents the results of research aimed at checking of educational-therapists self-esteem, and what the professional competencies cited as the most important, and which as least important in working with students with special educational needs in different areas of educational space.